Perancangan Sistem Informasi Manajemen Modul Layanan Pada Rumah Sakit - Gamaswara, Primanggara; Sudana, A.A.K Oka; Mandenni, Ni Made Ika Marini (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015, 2015)
Management System Information is one of tools used by organizations or companies to provide information for support several function of operation, management, and problem solver immediately and appropriately. Management System Information is needed by an organization or a large company such as hospital. Management System Information had designed for hospital necessary is formed by several modules in accordance with their respective functions, such as the Service Module. Management System Information of Hospital Service Module is expected to reduce hospital employees for working which several services still going manually paperbased, such as recording a patient's medical record. A method is used for this project called TAS Method who had five stages of design. Design of Management System Information of Hospital Service Module has been connected to six others module through exchanged data between module so that produce a integrated. Some process can be explained from this Service Module is Master Data Management, Treatment, Emergency Unit, Medical support, Medical Record, Scheduling, and Report. The result from designing this system is Exchanged Data Between Module Design, Context Diagram, Data Flow Diagram, Hierarchy Chart, Physical Data Model, and Graphical User Interface.